TATA NIAGA KETELA POHON YANG MENGUNTUNGKAN KEPADA PETANI - Agus Dwi Nugroho; Any Suryantini; Dumairy Dumairy; Revrisond Baswir (JURNAL AGRICA, 2018)
Cassava is one of the national prime commodities but its development has some obstacles, especially in marketing. The aims of this research were 1) to know the channels and its marketing efficiency, and 2) to know the need of developing the cassava trading system that benefits the farmers. The respondents are 30 farmers and traders in Wonogiri Regency. The results showed there were 3 marketing channels of cassava, channel 1 : farmers → mocaf processed flour companies → food companies → retailers → consumers; channel 2 : farmers → collecting traders → mocaf processed flour companies → food companies → retailers → consumers; and channel 3: farmers → retailers → consumers. The most efficient and profitable marketing is the farmers sell cassava to mocaf processed flour companies. Problems in marketing cassava include defective easily products, seasonal production, cassava prices at farmers is low and the benefits of marketing traders are huge. To improve the farmers' efforts, its need government policy to support through extensification and intensification, incentive policy on cassava pricing at farmer level (floor price), and farmer group empowerment (assistance of processed products, equipment aid and establish marketing institution).